PERAN ELITE KENEGERIAN KOPAH KECAMATAN KUANTAN TENGAH PADA PEMILIHAN KEPALA DAERAH DAN WAKIL KEPALA DAERAH KABUPATEN KUANTAN SINGINGI TAHUN 2011 - Suhamdani "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Country of Kopah represent one of the country exist in region district of Kuantan Tengah of Sub-Province Kuantan Singingi which consist of 5 countryside that is countryside of Kototuo, countryside of Kopah, countryside of Jaya and countryside of Munsaloh. Role of my me custom, peripheral of countryside, and prominent other society like BPD representing country elitee of Kopah very is influencing decision of resident in taking choice. This matter can be seen from result of legislative general election and election of regional leader and proxy regional leader in country of Kopah district of Teluk Kuantan where resident of country of Kopah support candidate of Party Association of Development (PPP) at legislative general election and support couple H. Sukarmis and of Drs. H. Zulkifli, M.Si carried by Party Functional Group at election of regional leader and proxy regional leader period 2011-2016 some times ago. Result of from management of legislative general election 2009 with election of regional leader and proxy regional leader Sub-Province Kuantan Singingi Year 2011-2016 happened change of country society support of Kopah to political party result of legislative general election of year 2009.As for intention of this research is to know role of elitee country of Kopah district of Teluk Kuantan at election of regional leader and proxy regional leader Sub-Province Kuantan Singingi Year 2011.This research is conducted by in country of Kopah district of Kuantan Tengah of Sub-Province Kuantan Singingi which consist of 5 countryside that is countryside of Koto tuo, countryside of Kopah, countryside of Jaya, Countryside of Munsalo and Countryside of Pulau Baru. Technique intake of data use interview that is in the form of raised question verbally to responder for the equiping of date. Responder to interview in this research consist of countryside secretary and head, member and chief of BPD and custom figure.Result of research which is writer do is role all country elitee of Kopah district of Teluk Kuantan in socialization at election of regional leader and proxy regional leader Sub-Province Kuantan Singingi year 2011-2016 is to introduce candidate in formal forum which conducted by governance elitee and of forom without ceremony by custom figure elitee. Making sosilisasi as step early in supported candidate winning it. Role all elitee in participating in election of regional leader and proxy regional leader Sub-Province Kuantan Singingi year 2011-2016 conducted in the form of following active invite elector to chosen one of the candidate joined in in execution of campaign to draw society sympathy so that chosening supported by couple is election day moment. While role all elitee in social control of moment election of regional leader and proxy regional leader Sub-Province KuantanSingingi year 2011-2016 where country elitee of Kopah which divided in two successful team of victory unable to become mow voice one of the candidate although have conducted function and its its in observation through social control or order which doing by country elitee.Keywords: Role and Elite